Kompetensi Pedagogik Guru Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Di SMP Negeri 4 Batudaa Pantai - Bilale, Ida Safitri; Hafid, Radia; Sudirman, Sudirman; Panigoro, Meyko; Maruwae, Abdulrahim (State University of Gorontalo, 2025)
This study aims to determine the influence of teachers’ pedagogical competence on student learning outcomes in Social Studies at SMP Negeri 4 Batudaa Pantai. Pedagogical competence refers to a teacher's ability to manage learning processes, including understanding student characteristics, implementing effective teaching strategies, and evaluating learning outcomes. Using a quantitative descriptive method, data were collected through questionnaires distributed to 43 students. The results show a significant influence of teachers’ pedagogical competence on student learning outcomes, with a determination coefficient of 32.5%. This finding indicates that pedagogical competence contributes meaningfully to student academic achievement. The study recommends efforts to enhance pedagogical skills among teachers to improve student performance.Keywords: Teacher pedagogical competence,student’s learning outcomes.